Down‐regulation of MTHFD2 inhibits NSCLC progression by suppressing cycle‐related genes. Issue 2 (28th November 2019) - Yu, Chang; Yang, Lehe; Cai, Mengsi; Zhou, Feng; Xiao, Sisi; Li, Yaozhe; Wan, Tingting; Cheng, Dezhi; Wang, Liangxing; Zhao, Chengguang; Huang, Xiaoying
Abstract: Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) is a bifunctional enzyme located in the mitochondria. It has been reported to be overexpressed in several malignancies. However, the relationship between the expression of MTHFD2 and non‐small cell lung cancer (NSCLC) remains largely unknown. In this study, we found that MTHFD2 was significantly overexpressed in NSCLC tissues and cell lines. Knockdown of MTHFD2 resulted in reduced cell growth and tumorigenicity in vitro and in vivo. Besides, the mRNA and protein expression level of cell cycle genes, such as CCNA2, MCM7 and SKP2, was decreased in MTHFD2 knockdown H1299 cells. Our results indicate that the inhibitory effect of MTHFD2 knockdown on NSCLC may be mediated via suppressing cell cycle‐related genes. These findings delineate the role of MTHFD2 in the development of NSCLC and may have potential applications in the treatment of NSCLC.